look at the pattern:
salary now
=salary(0) = 3000
salary after 1 year
= salary(1) = 300 + 3000
salary after 2 years
= salary(2) = 2(300) + 3000
....
salary after n years
= salary(n) = n(300) + 3000
A)
salary(n) = 300n + 3000
so now just plug in whatever number of years for n
B)
so if n=4
salary(4) = 300(4) + 3000 = 4200
Hi I need help with this question please.
The base salary for a job is $3,000 per month. For each full year a person holds the job the salary increases by $300 per month.
A) Write as a function where x is years worked and y is the total monthly salary.
B)Solve the function if the person has worked for 4 years.
I do not understand how to do this question please help
1 answer